Does obesity hurt your wages more in Dublin than in Madrid? Evidence from ECHP - Beatrice d'Hombres; Giorgio Brunello (Institute for the Study of Labor (IZA), 2005)
We use data from the European Community Household Panel to investigate the impact of obesity on wages in 9 European countries, ranging from Ireland to Spain. We find that the common impact of obesity on wages is negative and statistically significant, independently of gender. Given the nature of European labor markets, however, we believe that a common impact is overly restrictive. When we allow this impact to vary across countries, we find a negative relationship between the BMI and wages in the countries of the European olive belt and a positive relationship in the countries of the beer belt. We speculate that such difference could be driven by the interaction between the weather, BMI and individual (unobserved) productivity.
Keywords: I12; J3; 330; wages; body mass index; Europe